The genetic profile of combat sport athletes: a systematic review of physiological, psychological and injury risk determinants - Anastasiou, K.; Morris, M.; Akam, L.; Mastana, S. (International Journal of Environmental Research and Public Health, 2024)
This systematic review aims to assess the genetic determinants influencing combat sports performance and address potential gaps in previous reviews. Twenty-four selected studies were analysed, investigating genetic influences on physiological performance, psychological traits, psychophysiological factors like pain perception, and injury susceptibility in combat sport athletes. The systematic literature search, using keywords, encompassed PubMed, Scopus, SportDiscus, Medline, and Google Scholar. The Covidence systematic review management software facilitated the screening process and the creation of the PRISMA flow diagram. The quality assessment complied with the PRISMA guidelines, featuring a custom 10-point scale and the STREGA criteria for more reliable study inclusion. Collectively, the 24 studies incorporated 18,989 participants, of which 3323 were combat athletes of majority European ancestry (71.7%) from various combat sports disciplines. Twenty-five unique genetic variants were significantly associated with combat sports performance across diverse domains. These included physiological performance (nine genetic variants), psychological traits (ten genetic variants), psychophysiological factors (one genetic variant), and injury susceptibility (four genetic variants). In conclusion, this systematic review lays the foundation for a more comprehensive exploration of the association between genetics and athletic performance in the demanding arena of combat sports, offering valuable insights for talent identification, training optimisation, and injury prevention.